Numerical Study of Ducted Turbines in Shallow Water Environment - Rosli, Azzim; Abdul Rahman, Anas; Abdul-Rahman, Ayu; Marzuki, Najwa Syafiqa; Fadhli, Wan Muhammad; Misran, Syafiq; Ramadhan Basiddiq, Ramadhan Ahmed (International Journal of Integrated Engineering, 2023)
The development of tidal turbines, particularly for shallow water applications, is still in its early stages. Vertical axis tidal turbines (VATT) are often preferred for shallow water due to the bidirectional nature of tidal currents. Implementing a channelling system around a tidal turbine can significantly stabilise the flow field, increase the current velocity, and enhance the energy efficiency of the turbine. However, there has been limited exploration of using channelling techniques to improve the performance of VATTs in turbid areas. This study employs a numerical analysis using computational fluid dynamics (CFD) to investigate VATTs. The VATT model is represented by a cylindrical object with a diameter and height of 5 meters. The simulation focuses on the wake characteristics and the design of turbine arrays. The Reynolds-Averaged Navier-Stokes (RANS) equations are utilised as flow viscous solvers in ANSYS Fluent, and the effectiveness of the ducts in energy conversion is calculated using the realizable two-layer turbulence model. The primary objective of this study is to examine the impact of converging devices on tidal turbine performance and propose an optimal design for shallow water applications. The proposed ducted design shows an increase in current speed passing through the device by 11.1%. Although the wake generated by the multi-row staggered array layout disperses the flow to the side of the domain, the model demonstrates a 0.9% improvement in velocity magnitude. Conversely, the results for the single-row inline layout indicate the most favorable arrangement for shallow water applications, with a 19.4% increase in velocity magnitude and a shorter wake generation.